How Behavioral Finance during Pandemic COVID-19? - Asri Solihat; Nugraha Nugraha (Jurnal Inovasi Bisnis dan Kewirausahaan, 2020)
The global pandemic of COVID-19 has created dramatic and unprecedented challenges for individuals, the economy, financial markets, financial institutions and governments. The purpose of this study was to determine how much change in financial behavior during the COVID-19 pandemic. This study uses a literature review method by comparing several previous research findings that are relevant to the COVID-19 pandemic problem. The results of this study reveal changes in financial behavior during the COVID-19 pandemic, especially in urban areas that are in the red zone and many financial transactions.